Morphology of experimental antibiotic-associated enterocolitis in the hamster: a model for human pseudomembranous colitis and antibiotic-associated diarrhoea. Issue 6 (June 1979) - Price, A B; Larson, H E; Crow, J
Abstract : The morphology of antibiotic-associated enterocolitis in the hamster is described and compared with human antibiotic-associated pseudomembranous colitis. It is shown to be a caecal disease with proliferative mucosal changes and in this respect unlike the human counterpart. The bacteriology and toxicology, however, are identical. In addition, mucosal changes are described in animals on antibiotics but without established enterocolitis. As a result we suggest that there may be a spectrum of human disease ranging from mild antibiotic-associated diarrhoea to established pseudomembranous colitis. Therefore, despite the morphological variation, the hamster remains a good model for investigating the pathogenesis of pseudomembranous colitis and antibiotic-associated enteropathy in general.